STUDI TENTANG KAIN TENUN SERAWAI KOTA BENGKULU - ELIZA DWI MAYYANTI, Drs. Erwin, M.Sn, Drs. Abd. Hafiz,M.Pd (Serupa The Journal of Art Education, 2015)
The purpose of this study is to describe the motive’s shape, placement, meaning, and function of Serawai woven cloth. The method used is qualitative one with the descriptive approach. The results shows that the shape of weaving motifs composed of vertical stripes, horizontal, curved, zigzag, and flat plane. The forms are derived from the shape of the flora, fauna, nature, and geometric. The placement motifs on Serawai woven cloth namely: 1) The head cloth, 2) Edge of cloth, 3) Bottom cloth, and 4) Field of cloth. The meaning of Serawai decorative woven cloth is symbolic, natural evironment, means of livelihood, and customs and the ideals of life of local residents. It’s function is divided into a social function, culture, and life functions.Keywords: Form, Placement, Meaning and Function of Woven Fabrics Serawai Bengkulu City.